Clozapine Interaction with Phosphatidyl Inositol 3-Kinase (PI3K)/Insulin Signaling Pathway in Caenorhabditis elegans - Karmacharya, Rakesh (2009)
Clozapine has superior and unique effects as an antipsychotic agent, but the mediators of these effects are not known. We studied behavioral and developmental effects of clozapine in Caenorhabditis elegans, as a model system to identify previously undiscovered mechanisms of drug action. Clozapine induced early larval arrest, a phenotype that was also seen with the clozapine metabolite N-desmethyl clozapine but not with any other typical or atypical antipsychotic drug tested. Mutations in the insulin receptor/daf-2 and the phosphatidyl inositol 3-kinase (PI3K)/age-1 suppressed clozapine-induced larval arrest, suggesting that clozapine may activate the insulin signaling pathway. Consistent with this notion, clozapine also increased expression of an age-1::GFP reporter. Activation of the insulin signaling pathway leads to cytoplasmic localization of the fork head transcription factor FOXO/daf-16. Clozapine produced cytoplasmic localization of DAF-16::GFP in arrested L1 larvae, in contrast to stressors such as starvation or high temperature which produce nuclear localization of DAF-16::GFP in arrested L1 larvae. Clozapine also inhibited pharyngeal pumping in C. elegans, an effect that may contribute to but did not explain clozapine-induced larval arrest. Our findings demonstrate a drug-specific interaction between clozapine and the PI3K/insulin signaling pathway in C. elegans. As this pathway is conserved across species, the results may have implications for understanding the unique effects of clozapine in humans.